THE INFLUENCE OF TEAM COLLABORATION, ORGANIZATIONAL CULTURE, AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE - Chandra, Ferdian; Purnomo, Agus (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the influence of team collaboration, organizational culture, and work-life balance on employee performance at PT. Surveyor Indonesia, Lampung Regional Office. Amidst the increasing demands for operational efficiency and speed, companies must optimize their human resources through supportive work environments. This research employs a quantitative approach. The population includes all 43 employees of PT. Surveyor Indonesia Lampung, utilizing a saturated sampling technique (census) where the entire population serves as respondents. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that team collaboration, organizational culture, and work-life balance individually have a positive and significant effect on employee performance. Simultaneously, these three variables significantly influence employee performance with an F-value of 551.742. The Adjusted R Square value of 0.975 indicates that 97.5% of the variation in employee performance is explained by these variables, with organizational culture being the most dominant factor. This suggests that strengthening corporate values, fostering teamwork, and ensuring a balanced work-life are essential strategies for maximizing employee productivity.